Die Katechismen in der Schaffhauser Kirche - Bryner, Erich (Zwingliana, 2013)
When Johann Konrad Ulmer took up his pastorate in Schaffhausen in 1566, the traditional practice of religious training according to the catechism of Leo Jud, which had been taught ever since the reform had been accepted, was in trouble. Ulmer wrote his own catechism, however, the pastors in Schaffhausen did not accept it. Bullinger's mediation ended the conflict about the catechism in Schaffhausen, whereby the synod accepted the "Catechism for the Church and Schools of the City and Countryside of Schaffhausen", which was a combination of Ulmer’s own work and Jud’s Small Catechism. The Heidelberg Catechism replaced it in 1642. Schaffhausen printed its own printouts. The Heidelberg Catechism remained the tool for religious training for a long time and was highly praised. In the eighteenth century, Johann Wilhelm Meyer modeled a collection of literary verses after the text. Johann Hübner’s "Zweimal zweiundfünfzig biblische Geschichten" (printed in Schaffhausen in 1744) was a supplement to the instruction. The Heidelberg Catechism underwent sharp criticism at the end of the eighteenth century; critics argued the text was too difficult for children because its style was old fashion, its theology too dogmatic and not contemporary enough. Noteworthy theologians and educators passionately defended the Heidelberg Catechism, its form, language and theology, as well as the method of learning it by heart. The Heidelberg Catechism remained in the Schaffhausen Church well into the twentieth century as a useful tool for introducing Evangelical faith to the youth.